2007
DOI: 10.1626/pps.10.159
|View full text |Cite
|
Sign up to set email alerts
|

Response To Salinity In Rice: Comparative Effects Of Osmotic And Ionic Stresses

Abstract: : The effects of the osmotic component of salt stress on rice cultivar IR64 were examined. Treatments were four combinations of two levels of osmotic stress at two developmental stages: medium-and highlevel stress applied at the vegetative and reproductive stages using salt (NaCl) and polyethylene glycol-6000 (PEG) as sources of osmotic stress. Both PEG and NaCl reduced the total above ground biomass and delayed flowering and maturity, with a longer delay observed with the high-level stress. The reduction in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 29 publications
3
53
0
5
Order By: Relevance
“…Likewise, Castillo et al (2007), based on a study that evaluated the effect of osmotic and ionic stresses on the rice variety IR64, observed that the higher the salinity level of the solution, the greater the delay of rice development, which reached 19 days. Whereas the range for sowing most of the cultivars used in the State of Rio Grande do Sul is 30 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Castillo et al (2007), based on a study that evaluated the effect of osmotic and ionic stresses on the rice variety IR64, observed that the higher the salinity level of the solution, the greater the delay of rice development, which reached 19 days. Whereas the range for sowing most of the cultivars used in the State of Rio Grande do Sul is 30 days.…”
Section: Resultsmentioning
confidence: 99%
“…In salt levels above tolerable by rice plants, the water salinity causes a decrease in tillering and increases spikelet sterility (Ehrler, 1960). Several studies with different genotypes and different locations and environments (Fageria, 1991;Zeng et al, 2001;Grattan et al, 2002;Rodrigues et al, 2005;Melo et al, 2006) have shown a linear relationship between the increasing levels of salinity and the decrease in the number of tillers, in addition to increasing the number of non-productive tillers (Castillo et al, 2007). Salt stress also causes a reduction of photosynthesis, which occurs due to decreased availability of CO 2 inside the leaf, by closing the stomata.…”
Section: Introductionmentioning
confidence: 99%
“…Esse parece ter sido o caso nos tratamentos com PST de 10 e 20 %, mas não no de 5 %, que apresentou quantidade de material vegetal semelhante à do tratamento testemunha. Isso pode ter ocorrido pelo fato de, até determinado nível de salinidade, a compartimentalização do Na nos vacúolos poder evitar os efeitos deletérios desse elemento no citosol, mantendo o potencial osmótico da célula e minimizando o déficit hídrico em um ambiente salino (Castillo et al, 2007).…”
Section: Resultados E Discussão Salinidade Do Solo E Cátions Trocáveisunclassified
“…A maior concentração de Na no tecido, em função do cultivo de arroz em meio salino, impõe um estresse iônico sobre a cultura em adição ao estresse osmótico (Castillo et al, 2007). Neste estudo, esse fato é evidenciado pelos efeitos antagônicos entre os níveis de Na + adicionados ao solo e pela absorção de K pelo arroz (Quadro 8).…”
Section: Absorção De Cátions Pelo Arrozunclassified
See 1 more Smart Citation